Pengaruh Urbanisasi Dan Kontribusi Sektor Jasa Terhadap Penerimaan Pajak Dengan Kualitas Peraturan Sebagai Variabel Moderating - Praja, Rama Bhaskara; Wijaya, Suparna (Jurnalku, 2023)
Taxes are the backbone of a country's revenue, especially developing countries. The higher the tax revenue, the higher the country's ability to fund various government activities such as education, health, defense, social welfare programs, public infrastructure projects, and others. lower-middle income countries have less tax revenue than upper-income countries. Therefore, it is important to find the factors that influence tax revenues in lower-middle income countries. This research was conducted using linear regression with panel-corrected standard errors or known as PCSE. The results of the study show that simultaneously urbanization, the service sector and the moderating variable in the form of the quality of regulations affect tax revenues significantly. While partially, the urbanization has a positive effect on tax revenues. On the other hand, the service sector and regulatory quality have a negative effect on tax revenues. From the results of the moderation regression analysis, it was found that the quality of regulations does not moderate the effect of urbanization on tax revenues. On the contrary, from the interaction with the service sector, it is found that the quality of regulations weakens the negative influence of the service sector on tax revenues.